Applying Sharīʿa in post-revolutionary Egypt: theory and practice revisited - Mostafa, Mohammed Sameh Mohammed (AUC Knowledge Fountain, 2013)
Theoretically, Sharīʿa is meant to be an applicable methodology of jurisprudence that governs the state legal system. Applying Sharīʿa, or calling for its application, is, further, a must for those who believe in its divinity. In the process of democratic transition in Egypt, Islamists proposed applying Sharīʿa, claiming that its mere application provides accurate solutions for the chronic problems Egypt has long been suffering from. However, the obligatory nature of applying Sharīʿa and its positive impact on the community’s total welfare are not absolute paradigms. The conditions of the society in which applying Sharīʿa is proposed should be thoroughly recognized. As with any legal system, attaining the positive outcomes of applying Sharīʿa depends on the extension to which law is dominant in society. And since “law” does not “rule” in Egypt, at least in the formal liberal sense of the term, then neither applying Sharīʿa nor any other methodology would diffuse its underlying ideology. Therefore, this thesis examines the promises and limitations of applying Sharīʿa in post-revolutionary Egypt, on both the theoretical and practical levels, and highlights the major factors that neutralized the rule of law in Egypt so far thereby undermining the claims of applying Sharīʿa today.